FORMULATION OF CHITOSAN ALGINATE NANOPARTICLES CONTAINING ETHANOL EXTRACT OF KEPUNDUNG LEAVES (BACCAUREA RACEMOSE) AND EVALUATION OF BLOOD GLUCOSE LOWERING ACTIVITY IN VITRO AND IN VIVO - Luh Gede Wiwin Pebriani, Ni
Kepundung (Baccaurea racemosa) is a plant that is not commonly cultivated, but it has potential as a herbal medicine, including the potential for lowering blood glucose levels related to diabetes. Flavonoid compounds from the ethanol extract of kepundung leaves (EEDK) show activity as ?-glucosidase inhibitors, but this activity still needs to be enhanced. Moreover, flavonoids have limitations due to low bioavailability, preventing them from providing optimal therapeutic effects for the body. This study aimed to enhance EEDK activity by encapsulating EEDK in chitosan-alginate nanoparticles (NKA-EEDK). The NKA-EEDK formulation was designed using the Box Behnken Design method on the Minitab21® application, with independent variables being surfactant concentration (X1), STTP concentration (X2), and ultrasonication time (X3). The dependent variables used were particle size (Y1), polydispersity index (Y2), and encapsulation efficiency (Y3). The optimal NKA-EEDK formulation was characterized and tested for its activity through in vitro ?-glucosidase inhibitor testing and in vivo glucose tolerance testing. The optimal NKA-EEDK formulation consisted of chitosan (0.6%), poloxamer 407 (1%), EEDK (0.6%), STPP (0.23%), and alginate (0.675%). The preparation process involved stirring at 700 rpm and ultrasonication for 15 minutes. The optimal NKA-EEDK preparation had the following characteristics: particle size of 182.8 ± 10.1 nm, polydispersity index of 0.296 ± 0.02, zeta potential of -16.4 ± 1.5 mV, preparation pH of 5.8 ± 0.03, encapsulation efficiency of 84.74 ± 0.44%, particle morphology that approached spherical, and a release percentage of 78.31 ± 2.48% over 24 hours. NKA-EEDK demonstrated good stability at 25°C for 21 days. NKA-EEDK showed better glucose-lowering activity compared to EEDK, both in vitro and in vivo.